RESEARCH NOTE Analysing the impact of marriage on women’s behavior and self development in Uttar Pradesh, India - Gaurav Sankalp,; Shalini Agrawal, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2012)
Marriage is a relation between man and woman to have legitimate sex and legitimate children but above these goals it is to give mutual support and contribute to mutual success. In India the impact of marriage on women can be more visible than that of men because Indian woman has to leave her parents home and move into her husband’s home after marriage. This means a complete change of environment. This study sought to trace some of the main features of the impact of this change among 250 married women of Uttar Pradesh. In particular it sought possible answers to questions such as the right age for the marriage and to evaluate the changes in behavior of the women after marriage. It was found that marriage age after 25 was better for the self development of women, that marriage did develop women to become more responsible, that there was behavioral change of woman after marriage, and that married women perceived a greater satisfaction with life. Nevertheless for further empowerment married women should acquire better skills in decision making, communication and problem solving.